Double stator type permanent magnet generator - Misron, Norhisam; Masruni, Norafiza; Sia, Chee Yap (IEEE, 2009)
This paper discussed on development of double stator type permanent magnet generator (DSPMG). Basically, the DSPMG is a slot type topology and operated in a single-phase. The DSPMG used a new type of internal permanent magnet topology rotor configuration. The Finite Element Method (FEM) was used to analyze the DSPMG performance and various numbers of poles and rotor size were considered during this analysis. The result shows that the output power of DSPMG is influence by these design parameters. Finally, a new type of DSPMG was developed at end of this research.